Bioprinting of Collagen Type I and II via Aerosol Jet Printing for the Replication of Dense Collagenous Tissues - Gibney, Rory; Ferraris, Eleonora (Frontiers in Bioengineering and Biotechnology, 2021)
Collagen has grown increasingly present in bioprinting, however collagen bioprinting has mostly been limited to the extrusion printing of collagen type I to form weak collagen hydrogels. While these weak collagen hydrogels have their applications, synthetic polymers are often required to reinforce gel-laden constructs that aim to replicate dense collagenous tissues found in vivo. In this study, aerosol jet printing (AJP) was used to print and process collagen type I and II into dense constructs with a greater capacity to replicate the dense collagenous ECM found in connective tissues. Collagen type I and II was isolated from animal tissues to form solutions for printing. Collagen type I and II constructs were printed with 576 layers and measured to have average effective elastic moduli of 241.3 kPa ± 94.3 kPa, and 196.6 kPa ± 86.0 kPa (± SD), respectively, without any chemical modification. Collagen type II solutions were measured to be less viscous than type I and both collagen type I and II exhibited a drop in viscosity due to AJP. Circular dichroism and SDS-PAGE showed collagen type I to be more vulnerable to structural changes due to the stresses of the aerosol formation step of aerosol jet printing while the collagen type II triple helix was largely unaffected. SEM illustrated that distinct layers remained in the aerosol jet print constructs. The results show that aerosol jet printing should be considered an effective way to process collagen type I and II into stiff dense constructs with suitable mechanical properties for the replication of dense collagenous connective tissues.